Effect of Academic Grade Level on Return to Athletic Competition After Anterior Cruciate Ligament Reconstruction. Issue 4 (April 2019) - Bauer, Matthew; Feeley, Brian T.; Gallo, Robert A.
Abstract : Background: After anterior cruciate ligament (ACL) reconstruction, 63% to 87% of high school athletes return to competition. Although physical and psychological factors are known contributors for failure to return to play, little attention has been paid to effect of academic grade level. Our purpose was to determine the influence of effect of academic grade level on return to competitive play. The primary hypothesis is that high school seniors who undergo ACL reconstruction or knee arthroscopy will be less likely to return to competitive play at 1 year than those in grades 9 to 11. Methods: We retrospectively reviewed high school athletes who injured their knee during competitive athletic activity and underwent arthroscopic knee surgery, including ACL reconstruction. We included those 14 to 18 years old at time of surgery and analyzed records for grade level, sporting activity, surgery details, and date of return to play. The definition of return to competitive play was return to same preinjury sport within 1 year of surgery and the sport had to be organized. Results: Our study group included 225 patients that underwent an ACL reconstruction and 74 had knee arthroscopy. Athletes undergoing ACL reconstructions were less likely to return to preinjury sport within 1 year than those undergoing knee arthroscopy ( P =0.0163). Seniors were significantly less likely to return to play at 1 year than athletes in grades 9 to 11 after both ACL reconstruction ( P <0.0001) and knee arthroscopy ( P =0.0335). Although return to competitive play rates remained fairly constant within grades 9 to 11, a precipitous decline by 28.9% and 29.4% in return to play rates occurred in the ACL reconstruction and knee arthroscopy groups, respectively, between the junior and senior years of high school. Discussion: Although return to competition rates were lower for high school athletes undergoing ACL reconstruction than those undergoing knee arthroscopy, both had declines in return when the surgery occurs during their senior season. These data are useful when interpreting return to play rates. Future studies would benefit from further defining this relationship, or at least, noting the number of "senior" athletes studied. Level of Evidence: Therapeutic study—Level III.